ECONOMIC EFFICIENCY OF PRE-SOWING TREATMENT OF SOFT WINTER WHEAT SEEDS WITH THE ELECTRO ACTIVATED SOLUTIONS - E. N. Simonova (Зерновое хозяйство России, 2018)
The article considers the innovative ecologically friendly methods of pre-sowing treatment of soft winter wheat seeds ‘Donskoy Mayak’, one of which was the use of the electro activated solutions received during the electrolysis of sodium chloride solution. During the study we carried out a comparative assessment of economic efficiency of the pre-sowing treatment of the seed material with the chemical ‘Premis-200’ and with the use of the electro activated solutions. The article shows the economic profitability of the electro activated solutions in the cultivation of winter wheat. The researches established that the total economic profit of the treatment of seed with the electro activated 1% solution of active chloride was more than 3.000 rubles per ha in comparison with the chemical ‘Premis-200’. It has been determined that the coefficient of the energetic efficiency of winter wheat cultivation technology is higher after the treatment with the electro activated solution, than with the chemical ‘Premis-200’.